Self-efficacy and its relationship to impression management among educational counselors (Journal of the College of Basic Education, 2025)
The current research aims to identify self-efficacy and impression management among educational counselors, and to identify the significance of the difference among educational counselors according to the gender variable (male-female).as well as to identify the correlation between these two variables. To achieve the research objectives, a tool was built to measure self-efficacy, and a tool was built to measure impression management by the researcher. The two scales were applied to the research sample of (250) male and female counselors, and after processing the data using appropriate statistical methods, the results showed the following:Educational counselors have a good level of self-efficacy.-Educational counselors have impression management.--There are no statistically significant differences in each of (self-efficacy and impression management) among educational counselors according to the gender variable(males – females).-There is a positive direct correlation between self-efficacy and impression management among educational counselors.The researcher presented a number of recommendations and suggestions